(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The epichoric scripts of the Iberian Peninsula can be grouped by their internal characteristics in two large groups: the northern scripts, almost completely deciphered, and the southern ones, which still have many signs without consensus values. The first group is made up of the north-eastern Iberian script, with dual standard, dual extended and non-dual variants, and of the Celtiberian script, with eastern and western variants, and each of them in turn with dual and non-dual variants. The second group basically includes the south-eastern Iberian script, apparently always dual, and the south-western script, clearly non-dual. However, everything points to the existence of other southern scripts still to be categorized. Among them are The Espanca script and a small group, located mainly in the Guadalquivir Valley that have common characteristics and that we are already beginning to identify under the denomination of Turdetanian. Both families share a common ancestor, which would probably stem from the Phoenician alphabet, and that would justify the common characteristics of the two families: a similar corpus of signs, the coexistence of alphabetical and syllabic signs and the use of dualities to represent similar sounds by means of adding marks to the same base sign.